2020
DOI: 10.1007/s11356-020-10680-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bacterial aerosol, particulate matter, and microclimatic parameters on animal welfare in Chorzów (Poland) zoological garden

Abstract: Zoos are very popular facilities visited by entire families with children, who come there to watch live animals. Zoos also provide workplaces for a large number of people directly looking after the animals. For places designed to house animals, regardless of whether they are farm animals, pets, or zoo animals, a higher concentration of both dust and potentially harmful bioaerosols can be expected. Unfortunately, there are almost no studies concerning the concentration of bacterial bioaerosols and particulate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The research conducted previously in the same object (Grzyb and Pawlak 2021 ) revealed that I/O ratio for bacteria reached maximum value of 344 for TC and 785 for RF. In the case of indicator bacteria, ST-POS in particular, I/O ratio reached the value of 11,029 for TC and 8979 for RF.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The research conducted previously in the same object (Grzyb and Pawlak 2021 ) revealed that I/O ratio for bacteria reached maximum value of 344 for TC and 785 for RF. In the case of indicator bacteria, ST-POS in particular, I/O ratio reached the value of 11,029 for TC and 8979 for RF.…”
Section: Discussionmentioning
confidence: 66%
“…This study is a continuation of previous experiments carried out in the zoo in Kraków: in the first, focused on bacterial bioaerosol (Grzyb and Lenart-Boroń 2019 ); in the second, focused on fungal bioaerosol (Grzyb and Lenart-Boroń 2020 ). The third work again concerns bacterial bioaerosol, but in a different facility: at the zoo in Chorzów (Grzyb and Pawlak 2021 ). In the present work, the indicator bacteria will be introduced as ingredients of bioaerosols.…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted previously in the same object(Grzyb and Pawlak 2021) revealed that I/O ratio for bacteria reached maximum value of 344 for TC and 785 for RF. In the case of indicator bacteria, ST-POS in particular, I/O ratio reached the value of 11,029 for TC and 8,979 for RF.…”
mentioning
confidence: 54%
“…Contradictory results were obtained in the facilities in other zoological garden-in Chorzów. In that case, RF share was even higher and amounted to 74% for giraffes and as much as 86% for camels (Grzyb and Pawlak 2021).…”
Section: Discussionmentioning
confidence: 91%